Cambios en el pelaje del roedor subterráneo Ctenomys talarum: posible mecanismo térmico compensatorio. - Cutrera, Ana Paula (2004)
In this work, the changes in fur density and length in the subterranean rodent Ctenomys talarum were evaluated as a possible compensatory mechanism during seasonal temperature changes in their burrow environment and during pregnancy in females, both situations being thermoregulatory challenging in this species. The ventral fur was shorter and less dense than the dorsal fur in the three groups (males, non pregnant females and pregnant females) and in the two seasons evaluated. Ventral and dorsal furs were significantly shorter during the warm seasons in the three groups. In the warm season, pregnant females had a ventral fur significantly shorter than that of males and non-pregnant females. The possible thermal advantages that the observed fur changes might represent for the species are discussed, with emphasis on the constraints imposed by the subterranean environment on available ways of dissipating body heat.